The Politics of Law on the Fulfillment of Restitution Rights for Rape Victims Based on the Qanun Jinayat in Aceh - Aljamalulail, Syarifah Rahmatillah; Rani, Faisal A; Muazzin, Muazzin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
This study aims to explore the policy of the politics of law and procedure for the effective fulfillment of restitution rights for rape victims in Aceh. For rape victims, restitution is a form of compensation as part of the fulfillment of human rights and legal protection for the disadvantaged party. Providing compensation for rape victims is crucial as generally the victims come from vulnerable groups who have been harmed physically, psychologically, and socially. However, the mechanism for obtaining compensation in the form of restitution for rape victims has been an issue in Aceh. In addition, the question arises on how the implementation of restitution is in the decisions of judges who try rape cases based on the Qanun Jinayat. This study used a normative juridical method, analyzed with the theory of legal politics. The study concludes that the regulation of restitution in the Qanun Jinayat as an additional punishment for rapists needs to be further studied to examine whether restitution as an additional punishment can fulfill a sense of justice for the victims. Moreover, the restitution formulation in the Qanun Jinayat Aceh has not made it easy for rape victims to receive compensation from the perpetrators due to the complicated process and requirements for obtaining restitution. However, in the context of legal politics, the Qanun Jinayat can be understood as a government policy to provide legal certainty and justice. Any shortcoming at present means that more room for improvements in its implementation in the future.